Some Interesting Consequences From Newton’s Modified Expression of Gravitational Force in the Vector Model for Gravitational Field - On, Vo Van (Communications in Physics, 2009)
In this paper, based on the Vector model for gravitational field we show some interest- ing consequences from Newton’s modified expression of gravitational force: dividing the space into regions around galaxies, maximal size of stable galaxies.